Exosomes containing ErbB2/CRK induce vascular growth in premetastatic niches and promote metastasis of bladder cancer. Issue 7 (24th June 2019) - Yoshida, Kazuhiko; Tsuda, Masumi; Matsumoto, Ryuji; Semba, Shingo; Wang, Lei; Sugino, Hirokazu; Tanino, Mishie; Kondo, Tsunenori; Tanabe, Kazunari; Tanaka, Shinya
Abstract: Locally advanced and metastatic invasive bladder cancer (BC) has a poor prognosis, and no advanced therapies beyond cisplatin‐based combination chemotherapy have been developed. Therefore, it is an urgent issue to elucidate the underlying mechanisms of tumor progression and metastasis of invasive BC for the development of new therapeutic strategies. Here, we clarified a novel role of exosomes containing ErbB2 and CRK in a formation of premetastatic niches and subsequent metastases. CRK adaptors were overexpressed in invasive UM‐UC‐3 BC cells. In an orthotopic xenograft model, metastases to lung, liver, and bone of UM‐UC‐3 cells were completely abolished by CRK elimination. Mass spectrometry analysis identified that ErbB2 was contained in UM‐UC‐3‐derived exosomes in a CRK‐dependent manner; the exosomes significantly increased proliferation and invasion properties of low‐grade 5637 BC cells and HUVECs through FAK and PI3K/AKT signaling pathways. In athymic mice educated with UM‐UC‐3‐derived exosomes, i.v. implanted UM‐UC‐3 cells were trapped with surrounding PKH67‐labeled exosomes in lung and led to development of lung metastasis with disordered vascular proliferation. In contrast, exosomes derived from CRK‐depleted BC cells failed to induce these malignant features. Taken together, we showed that CRK adaptors elevated the expression of ErbB2/3 in BC cells, and these tyrosine kinase/adaptor units were transferred from host BC cells to metastatic recipient cells by exosomes, leading to vascular leakiness and proliferation and contributing to the formation of distant metastasis. Thus, CRK intervention with ErbB2/3 blockade might be a potent therapeutic strategy for patients with ErbB2 overexpressing advanced and metastatic BC. Abstract : CRK adaptors elevate the expression of ErbB2/3 in bladder cancer (BC) cells, and these tyrosine kinase/adaptor units are transferred from host BC cells to metastatic recipient cells by exosomes, leading to vascular leakiness and proliferation and contributing to the formation of distant metastasis. Thus, CRK intervention with ErbB2/3 blockade might be a potent therapeutic strategy for patients with ErbB2 overexpressing advanced and metastatic BC.